Why Do Larger Orders Receive Discounts on the London Stock Exchange? - Bernhardt, Dan; Dvoracek, Vladimir; Hughson, Eric; Werner, Ingrid M. (Review of Financial Studies, 2005)
We argue that competition between dealers in a classic dealer market is intertemporal: A trader identifies a particular dealer and negotiates a final price with only the intertemporal threat to switch dealers imposing pricing discipline on the dealer. In this kind of market structure, we show that dealers will offer greater price improvement to more regular customers, and, in turn, these customers optimally choose to submit larger orders. Hence, price improvement and trade size should be negatively correlated in a dealer market. We confirm our model's predictions using unique data from the London Stock Exchange during 1991. Copyright 2005, Oxford University Press.